Effectiveness of Performance Appraisal in the Motivation of Employees to Attain Good Performance at Power Tractire Incorporated, Caloocan City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Performance evaluation is effective and essential to team and individual success.Performance evaluations can increase motivation, working relationships, and the capacity forsuccession planning when they are conducted well. The study aimed to look into theeffectiveness of performance appraisal in motivating employees to attain good performance atPower Tractire Incorporated in Caloocan City. Power Tractire Incorporated (PTTI) isexperiencing a situation where there is a disagreement between the management and theiremployees, causing them to have challenges in delivering employee progress in aperformance appraisal that also affects the feedback towards their performance that alsoresults in the lack of enthusiasm at work.Based on the gathered data, the presented factor affecting employee motivation in terms ofrewards is "Strongly Agree" if they are fairly compensated for their work, and in terms ofCompliments, the achievement of employees are well appreciated and valued by themanagement is "Agree" while in terms of Work Environment, the job gives the opportunity tolearn more skills is "Agree." The Effectiveness of Performance Appraisal in terms of Feedbackis well explained and communicated to the employees and interpreted as “Strongly Agree,”while in terms of Progress, gaining new knowledge and skills is also “Strongly Agree,” and interms of Punctuality, the employee is present at work consistently, understand the value oftime, and do work on time without any delays, it is all interpreted as “Strongly Agree,” and thechallenges encountered by the employees in dealing with performance appraisal isdisagreement against co-workers/management.The researchers recommended that the employees should maintain their current status in thecompany because it leads to an increased chance of internal promotion and other benefits. Itis recommended that the company should focus on fairly compensated for their work in termsof rewards, the achievements of employees are well appreciated and valued by themanagement, and also the company should focus on job opportunities to learn more skills.
Keywords: Business